ACCOUNTING SYSTEMS FOR SMEs IN CULINARY TOURISM CENTERS IN SURABAYA - Yuli Ermawati; Mohammad Sodikin; Rodhiyah Rodhiyah; Heru Tjahjono (SEAN Institute, 2023)
The purpose of this study was to analyze the effectiveness of implementing a single cashier system at Culinary Tourism Centers in Surabaya, identify the opinions of MSMEs and visitors regarding the implementation of a single cashier system at Culinary Tourism Centers in Surabaya, and formulate an appropriate Accounting System Pattern for Culinary Tourism Centers in Surabaya. The results of the study are that the City Government through the Surabaya City Cooperative, Micro Business and Trade Office has made several improvements and empowerment to improve the quality of MSMEs in 49 Culinary Tourism Centers in Surabaya. The synergy between the government, companies and universities is the main key to the success of empowering MSME groups in Culinary Tourism Centers, especially for the effectiveness of implementing a single cashier system for SWK in Surabaya. The research team found the right integrated accounting system model for MSMEs at Culinary Tourism Centers in Surabaya. Going forward, the Dinkopdag should be more intense in providing motivation to MSMEs in SWK to rise from the pandemic situation and strengthen cooperation with companies and universities through their CSR both for simple accounting training and facilitating access to capital for MSMEs in SWK with an emphasis on digitizing the financial system, marketing services , and access to capital.